2019
DOI: 10.1371/journal.pone.0210811
|View full text |Cite
|
Sign up to set email alerts
|

Improving cost-efficiency of faecal genotyping: New tools for elephant species

Abstract: Despite the critical need for non-invasive tools to improve monitoring of wildlife populations, especially for endangered and elusive species, faecal genetic sampling has not been adopted as regular practice, largely because of the associated technical challenges and cost. Substantial work needs to be undertaken to refine sample collection and preparation methods in order to improve sample set quality and provide cost-efficient tools that can effectively support wildlife management. In this study, we collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 77 publications
1
23
0
Order By: Relevance
“…The hair samples used in this study were collected as references from captured coyotes and could therefore not be considered truly noninvasive, although the high success rate (100%) is promising for future applications using hair‐snares. Compared to the error rates of microsatellite genotyping (0%–48%) (Broquet & Petit, 2004), previous research has found that SNP‐based methods substantially reduce genotyping error rates to 1% (Kraus et al., 2015), 0.038% (Norman & Spong, 2015) and 0.29% (Bourgeois et al., 2019) when preselecting samples based on DNA concentration. Our total error rate from scat sample replicates was 1% without any preselection based on sample quality beyond selecting randomly from the subset of scats that yielded species ID via DNA metabarcoding.…”
Section: Discussionmentioning
confidence: 98%
“…The hair samples used in this study were collected as references from captured coyotes and could therefore not be considered truly noninvasive, although the high success rate (100%) is promising for future applications using hair‐snares. Compared to the error rates of microsatellite genotyping (0%–48%) (Broquet & Petit, 2004), previous research has found that SNP‐based methods substantially reduce genotyping error rates to 1% (Kraus et al., 2015), 0.038% (Norman & Spong, 2015) and 0.29% (Bourgeois et al., 2019) when preselecting samples based on DNA concentration. Our total error rate from scat sample replicates was 1% without any preselection based on sample quality beyond selecting randomly from the subset of scats that yielded species ID via DNA metabarcoding.…”
Section: Discussionmentioning
confidence: 98%
“…The hair samples used in this study were collected as references from captured coyotes and could therefore not be considered truly noninvasive, however, the high success rate (100%) is promising for future applications using hair-snares. Compared to the error rates of microsatellite genotyping (0-48%) (Broquet & Petit, 2004), previous research has found that SNP-based methods substantially reduce genotyping error rates to 1% (Kraus et al, 2015), 0.00038% (Norman & Spong, 2015) and 0.0029% (Bourgeois et al, 2019) when pre-selecting samples based on DNA concentration. Our total error rate for scats was 0.01% without any pre-selection based on sample quality beyond selecting randomly from the subset of scats that yielded species ID via DNA metabarcoding (85% of scats yielded a species ID).…”
Section: Discussionmentioning
confidence: 98%
“…Most studies on genotyping animal scats collected in the field highlighted the importance of using fresh scats to increase DNA quality (e.g. Murphy et al 2007;Vynne et al 2012;Lerone et al 2014;Bourgeois et al 2019). In the present study, we have already considered this factor and collected only otter faeces from the previous night.…”
Section: Discussionmentioning
confidence: 99%
“…Hájková et al 2006), storage duration until extraction of DNA (e.g. Soto-Calderón et al 2009;Bourgeois et al 2019) and diet of the defecating animal (Murphy et al 2003;Panasci et al 2011). Broad consensus was found regarding the age of the scat samples: genotyping success rates and sample quality were highest using the freshest samples (Piggott 2004;Murphy et al 2007;Brinkman et al 2010;Vynne et al 2012;Bourgeois et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation